SHARING PRACTICES AND DEMATERIALIZED SERVICES IN SMART CITIES - Riva Sanseverino, Eleonora; Riva Sanseverino, Raffaella; Vaccaro, Valentina (BDC. Bollettino Del Centro Calza Bini, 2016)
The “intelligent management” of the traditional areas of living the cities and of their urban functions, summarizes the model of smart city. Through new integrated approaches generated from the use of Information and Communication Technology (ICT) and of the web, which take the role of enabling tools for change, contemporary cities are strongly changing. The digital age creates, in fact, the conditions for the emergence of new tools and new services for citizens, based on communication and on sharing and participation practices. The article contextualizes these changes by focusing on some examples of what can be defined as “dematerialized services” of contemporary cities, seen as new urban services and new practices of community’s living in smart cities. Keywords: smart city, sharing practices, dematerialized services